Microbiological Profile, Shelf Stability and Some Physicochemical Properties of Fermented Flour from Different Sweet Potato Cultivars - C.F, Ezeama; J.U, Amajor (Journal of Food Technology Research, 2015)
Sweet potato flour was produced after fermentation of two cultivars (TIS87/0087 and TIS 2532.OP.1.13) of sweet potato (Ipomoea batatas) roots for 24h. The microbiological profile, pH and titratable acidity (TA) of the fermenting medium were assessed. The proximate composition and shelf stability of the ambient stored flour samples were also determined. Bacteria isolated from the fermenting medium were Lactobacillus plantarum, Streptococcus spp, Bacillus spp and Staphylococcus aureus while the fungal isolates included Penicillium spp. Rhizopus stolonifer, Aspergillus niger and yeast Saccharomyces cerevisiae. The Total Viable Count of both cultivars during fermentation differed significantly (P<0.05) only at 0h of fermentation. However, for TIS 87/0087 it ranged from 3.40 – 4.60 log10 cfu g-1 and 3.54 to 4.64 log10 cfu g-1 for TIS 2532.OP.1.13 cultivar. The lactic acid bacteria counts ranged from 2.40 to 3.60 log10 cfu g-1 for cultivar TIS87/0087 and 2.54 to 3.64 log10 cfu g-1 for cultivar TIS 2532.OP.1.13. The TA for both cultivars were observed to have increased from 0.51% to 4.96% for TIS 87/0087 and 0.40% to 4.04% for TIS 2532.OP.1.13 as fermentation progressed in relation to fall in pH. The proximate composition of flours from TIS87/0087 and TIS 2532.OP.1.13 showed low moisture content (10.76% and 11.37%), high dry matter (89.24% and 88.66%), carbohydrate (81.25% and 81.01%), protein (5.16% and 5.09%), fiber (0.76% and 0.64%) and crude lipid (0.68% and 0.47%) respectively. However, the protein and crude lipid content of TIS 87/0087 flour were higher. The fermented flour had an acceptable microbial load limit (<5log10 cfu g-1) and shelf life stability for 3 months under ambient storage. The fermented TIS 87/0087 flour can be recommended for incorporation into instant food and bakery products.